Improving Results of District Health Plans in Niger - Karamoko, Djibrilla; Lorenzo-Meiro, Montserrat; Randrianarivelo, Benjamina; Harati, Elissar Tatum (World Bank, Washington, DC, 2020)
The Ministry of Public Health (MOH) in Niger has used Rapid Results Initiatives (RRIs) to achieve targets for reproductive health and nutrition. Key outcomes of this approach include: • Mobilization of regions and districts to overcome constraints to assisted deliveries, family planning (FP), nutritional counseling and measles vaccination, and thus achieve Disbursement Linked Indicators (DLIs). • Collaboratively planned provision of mobile health services, door-to-door visits and outreach to remote and underserved areas, by health teams and communities. • Engagement of local leaders to help health centers increase coverage of services to women and children, including mapping of households with low uptake of health services; implementing social sanctions to reduce home births. • Inclusion of FP and assisted deliveries and other messages on reproductive health and nutrition in sermons of religious leaders. The Government of Niger has rated RRI as one of the top innovations in its national health plan. The MOH and the regions are bound by annual performance contracts to improve results using RRIs.